Collaborative Governance in Accelerating the Reduction of Stunting in Metro Cities Lampung Province - Wahdi Wahdi; Muh Ilham; Mansyur Achmad; Rizky Amalia (Yayasan Riset dan Pengembangan Intelektual, 2024)
Stunting is a multidimensional public health issue, requiring collaborative efforts from various stakeholders including government, academia, communities, private sector, and media for effective intervention. However, collaborative efforts in Kota Metro have been suboptimal due to sectoral egos among agencies and insufficient participation from non-government stakeholders. This research aims to analyze the governance of collaborative governance in accelerating the reduction of stunting in Kota Metro. The method used is qualitative, employing data collection techniques such as observation, interviews, and focused group discussions as primary sources, supplemented by secondary data from literature review and government documents in Kota Metro. Based on the findings, it can be concluded that collaborative governance in accelerating stunting reduction in Kota Metro, Lampung Province, is not yet optimal, particularly in the collaboration process. The roles of communities, academia, and the private sector are not fully optimized, as governmental roles dominate in collaborative governance in Kota Metro. The study recommends an ideal model of collaborative governance for accelerating stunting reduction in Kota Metro, Lampung Province, based on a modified collaborative governance model by Ansell and Gash, termed the